2021
DOI: 10.3389/fnut.2021.795888
|View full text |Cite
|
Sign up to set email alerts
|

Lysozyme Improves the Inhibitory Effects of Panax notoginseng Saponins on Phenotype Transformation of Vascular Smooth Muscle Cells by Binding to Ginsenoside Re

Abstract: Panax notoginseng saponins (PNS) have been used to treat cardiovascular diseases for hundreds of years in China. Lysozyme can bind to exogenous compounds and promote their activity. Nevertheless, knowledge of whether there is a synergistic role between lysozyme and PNS is far from sufficient. In this study, we show that the mixture of PNS and lysozyme synergistically inhibited platelet derived growth factor BB (PDGF-BB)-induced vascular smooth muscle cell (VSMC) viability, and in the five main components of PN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 39 publications
(50 reference statements)
0
6
0
Order By: Relevance
“…It is well studied that inhibiting the proliferation and migration of VSMCs could effectively inhibit the formation of AAA. ( 14 , 15 ) We found that silence of SMOC2 inhibited proliferation and migration of Ang II-treated VSMCs, whereas overexpression of SMOC2 had the opposite effect. These data demonstrated that SMOC2 may regulate the AAA developmental process by affecting the proliferation and migration of VSMCs.…”
Section: Discussionmentioning
confidence: 84%
“…It is well studied that inhibiting the proliferation and migration of VSMCs could effectively inhibit the formation of AAA. ( 14 , 15 ) We found that silence of SMOC2 inhibited proliferation and migration of Ang II-treated VSMCs, whereas overexpression of SMOC2 had the opposite effect. These data demonstrated that SMOC2 may regulate the AAA developmental process by affecting the proliferation and migration of VSMCs.…”
Section: Discussionmentioning
confidence: 84%
“…Previous studies [31] have demonstrated that inhibition of excessive VSMC phenotypic switch are benefits during arterial remodeling. Studies have proven that triterpenoid saponins repressed VSMC proliferation by inhibiting phenotype transformation [17,18]. Therefore, we focus on the biomarkers to investigate whether DB exerts a role by blocking the phenotype switch of VSMC.…”
Section: Discussionmentioning
confidence: 99%
“…Report has shown that astragaloside IV can inhibit the proliferation and migration of rat VSMC by targeting CDK2 [16]. Besides, panax noto-ginseng saponins present inhibitory effects in the phenotype transformation of VSMCs and suppress abdominal aortic aneurysm progression [17]. Furthermore, ginsenoside Re inhibits VSMC proliferation induced by PDGF-BB via the eNOS/NO/cGMP pathway [18].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been found the inhibitory effect of notoginseng saponins (NGS) on the proliferation of vascular smooth muscle cells, which is the pathological basis of many vascular diseases, could be promoted by binding to lysozyme. 29 Obviously, characterization and evaluation of noncovalent interaction between NGS and lysozyme is crucial to understanding their pharmacological activities. For direct MALDI analysis, an equal volume of lysozyme and NGS ligand were mixed and incubated at 38 C for 60 min.…”
Section: Introductionmentioning
confidence: 99%
“…Since it can bind with many small molecules, lysozyme is used for drug delivery in modern pharmaceutics. Recently, it has been found the inhibitory effect of notoginseng saponins (NGS) on the proliferation of vascular smooth muscle cells, which is the pathological basis of many vascular diseases, could be promoted by binding to lysozyme 29 . Obviously, characterization and evaluation of noncovalent interaction between NGS and lysozyme is crucial to understanding their pharmacological activities.…”
Section: Introductionmentioning
confidence: 99%